Psychiatric Evaluation of Organ Donor Candidates in a University Hospital and Their Anxiety, Depression and Quality of Life Levels - Izci, Filiz; Findikli, Ebru; Zincir, Serkan; Camkurt, Akif; Kizilkurt, Ozlem; Giynas, Ferzan; Akin, Emin Baris (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2017)
Objective: The aim of this study was to conduct a psychiatric evaluation of organ donor candidates and to investigate their levels of anxiety, depression and quality of life. Material and Methods: This study was performed between May 2015 and February 2016. It included 102 volunteers. The socio-demographic Data Collection Form, DSM-IV Clinical Interview Form - Clinical Version Structured for Axis Diagnoses (SCID-I/CV), Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), Symptom Checklist (SCL-90-R), and SF-36 Quality of Life Survey (SF-36) were administered to the patients. Results: The average age of the applicants was found to be 41.64 +/- 12.02, 42.2% (n=43) being male and 57.8% (n=59) being female. When it comes to the degree of affinity between potential donors and recipients, 57.8% (n=59) were first-degree relatives, 19.6% (n=20) were spouses, and 22.5% (n=23) were other relatives and/or close relations. By dividing donor candidates into groups by the degree of their affinity to recipients, there were statistically significant differences revealed between BDI, BAI and SCL-90-R total scores and interpersonal sensitivity subscale scores. Conclusion: As compared to the global average, the number of living donors is higher than cadaver donors; and donor candidates mostly comprise spouses and first-degree relatives. Therefore, family members and first-degree relatives who are affected directly or indirectly by the transplant process are exposed to social and psychological effects more as the donor candidates/donors. It is of crucial importance to evaluate the psychosocial states of donors, in addition to recipients, in order to manage the long-lasting transplant process, a treatment- and care-demanding one in a more appropriate way.
Keywords: Anxiety; depression; donor selection; organ transplant; quality of life